STUDI KONDISI ANGIN DAN GELOMBANG LAUT DI PELABUHAN PANTOLOAN, PALU SULAWESI TENGAH - Sri Ningsih; Ayusari Wahyuni; Muh Said L (JFT : Jurnal Fisika dan Terapannya, 2020)
Port construction at Pantoloan has influenced the condition of port and its environment. The hidro-oceanography process has influenced the condition of water, especialy to the wind and wave condition. This research was aimed to know wind condition and wave characteristic at Pantoloan, Palu, Central Sulawesi. The method used in this research was the measurement of wave current using quantitative data processing from the ECMWF (European Center For Medium-Range Weather Forecasts) website for 10 years. The study results showed that the highest wind speed is the wind blowing from the northwest at 1.34 m/s. Wind directions that have potential to generate waves are wind from the north, northwest, west and southwest. Meanwhile, deep sea waves that occurred most frequent on study location were waves from the north (23.92%), followed by the Southwest (35.70%), the Northwest (3.70%) from the West (4.65%), and the Northeast (18.83%), the South direction is (8.08%), the Southeast direction is (2.61%), and the East direction is (2.50%) with a wave  length interval of 0-0.3 m and a period of 5 - 7.5 seconds.